Investigation of regression rate end-burning typed hybrid rocket motor - Azami, Muhammad Hanafi; Abdullah, Nur Azam; Nordin, Norhuda Hidayah (2022)
Hybrid Rocket Motor (HRM) has a critical weakness that impacts performance: low regression rate. Due to this, extensive investigation has been done on end-burning type HRM to enhance the regression rate. Experimental works were conducted on the end-burning HRM compared to the conventional HRM. The present investigation is focused on single port HRM, paraffin wax, and gas oxygen as the fuel and oxidizer, respectively. The results show that combustion occurs only at the fuel end in end-burning mode, which permits the burning area and fuel mass flow rate to remain constant, enhancing the motor's performance and ensuring that the oxidizer-to-fuel ratio does not fluctuate. HRM performance has also been evaluated by calculating thrust and specific impulses. According to this study, end-burning HRM has a 33% less regression rate but around a 50% increase in thrust and specific impulse compared to conventional HRM. The low regression is due to the small initial combustion area. Mass flux is the more prominent factor in increasing the regression rate and thrust of the end-burning HRM compared to the fuel length. Further improvement to the design of the HRM can maximize the potential of the end-burning mode.